We will define the following variables to solve the problem: s: normal speed t: normal time We write the following system of equations: 6 = s * t 6 = (s + 3) * (t-7) Rewriting the equation two we have: 6 = s * t -7s + 3t -21 Substituting: s = 6 / t 6 = (6 / t) * t -7 (6 / t) + 3t -21 Multiplying both sides by t: 6t = 6t - 42 + 3t ^ 2 - 21t Rewriting: 3t ^ 2 - 21t - 42 = 0 We take the positive root: t = 7/2 + root (105) / 2 t = 8.62 h We look for the value of the speed: s = 6 / t s = 6 / 8.62 s = 0.696 km / h Answer: she did travel 0.696 kilometers per hour